The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/stul.12077
|View full text |Cite
|
Sign up to set email alerts
|

The participants as objects: Variation And Meaning Of First‐ And Second‐Person Object Encoding In Spanish

Abstract: Syntactic functions are best conceptualized as prototypical associations of features at a variety of formal and semantic levels, which elements in actual clauses will match to different extents. In Spanish, the prototypical (accusative) object has a third‐person, inanimate, non‐autonomous entity as its referent. The encoding of the direct participants, i.e. the first and second persons, as syntactic objects will entail a displacement from the prototype that can have significant functional and meaningful effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…Previous research studies on subject and object variation found similar results regarding the omission of pronominal subject (Aijón Oliva and Serrano 2013) and person object (Aijón Oliva 2017a, 2017b; Serrano 2017a, 2017b) variants 2…”
Section: Resultssupporting
confidence: 52%
“…Previous research studies on subject and object variation found similar results regarding the omission of pronominal subject (Aijón Oliva and Serrano 2013) and person object (Aijón Oliva 2017a, 2017b; Serrano 2017a, 2017b) variants 2…”
Section: Resultssupporting
confidence: 52%